Green Tea Extract to Prevent Colorectal Adenomas, Results of a Randomized, Placebo-Controlled Clinical Trial. (25th June 2022) - Seufferlein, Thomas; Ettrich, Thomas J.; Menzler, Stefan; Messmann, Helmut; Kleber, Gerhard; Zipprich, Alexander; Frank-Gleich, Stefanie; Algül, Hana; Metter, Klaus; Odemar, Frank; Heuer, Theodor; Hügle, Ulrich; et al.
Abstract : INTRODUCTION: Preclinical, epidemiological, and small clinical studies suggest that green tea extract (GTE) and its major active component epigallocatechingallate (EGCG) exhibit antineoplastic effects in the colorectum. METHODS: A randomized, double-blind trial of GTE standardized to 150 mg of EGCG b.i.d. vs placebo over 3 years was conducted to prevent colorectal adenomas (n = 1, 001 with colon adenomas enrolled, 40 German centers). Randomization (1:1, n = 879) was performed after a 4-week run-in with GTE for safety assessment. The primary end point was the presence of adenoma/colorectal cancer at the follow-up colonoscopy 3 years after randomization. RESULTS: The safety profile of GTE was favorable with no major differences in adverse events between the 2 well-balanced groups. Adenoma rate in the modified intention-to-treat set (all randomized participants [intention-to-treat population] and a follow-up colonoscopy 26–44 months after randomization; n = 632) was 55.7% in the placebo and 51.1% in the GTE groups. This 4.6% difference was not statistically significant (adjusted relative risk 0.905; P = 0.1613). The respective figures for the per-protocol population were 54.3% (151/278) in the placebo group and 48.3% (129/267) in the GTE group, indicating a slightly lower adenoma rate in the GTE group, which was not significant (adjusted relative risk 0.883; P = 0.1169). DISCUSSION: GTE was well tolerated, but there was no statistically significant difference in the adenoma rate between the GTE and the placebo groups in the whole study population.